Relevance of Prospect Theory to Transport Choice Modeling: a Rejoinder - Timmermans, Harry (European Journal of Transport and Infrastructure Research, 2012)
I was pleased to see that van de Kaa spelled out my comments on prospect theory and must have spent quite some time tracing back the references and conducting some additional qualitative research. The very purpose of my contribution to the workshop and the paper was to stimulate discussion and it seems to have succeeded in that regard.